Wireless location tracking in wireless sensor networks - Yang, Shiyi (2010)
Wireless sensor network (WSN) is an emerging technology for monitoring of physical world with a densely deployed network of sensor nodes. The main advantages of WSN include its low cost, rapid deployment, self-organization, and fault tolerance. It can be used in a variety of applications, such as environment monitoring, industrial sensing and diagnostics, military surveillance, navigation and control of mobile robots, and body sensor network for healthcare. Target tracking is one of the important applications of WSN. Due to the limited communication, computation, and sensing capabilities of WSN, it should rely on collaborative signal and information processing (CSIP) to dynamically schedule sensor resources and efficiently process distributed sensor measurement, to trade off tracking accuracy with sensor usage cost. This report summarizes the work on establishing a tracking algorithm to improve the accuracy of the target tracking for mobile sensing. Since the tracking model is based on Extended Kalman Filter (EKF), computational-efficient EKF implementation approaches are discussed. Robot localization and navigation methods are implemented by the program and discussed. Experimental data under different sensor scheduling schemes are compared.